2022
DOI: 10.20517/cdr.2021.102
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to immune checkpoint inhibitors in KRAS-mutant non-small cell lung cancer

Abstract: Non-small cell lung cancer (NSCLC) patients with Kirsten rat sarcoma viral oncogene homolog (KRAS) mutation are associated with significant clinical heterogeneity and a poor prognosis to standard NSCLC therapies such as surgical resection, radiotherapy, chemotherapies, and targeted medicines. However, the application of immune checkpoints inhibitors (ICIs) has dramatically altered the therapeutic pattern of NSCLC management. Clinical studies have indicated that some KRAS-mutant NSCLC patients could benefit fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 152 publications
(283 reference statements)
3
9
0
Order By: Relevance
“…Their study raised the important role of circRNA in immune resistance and provided a potential targeted pathway "hsa_circ_0020714/miR-30a-5p/SOX4" to overcome resistance to anti-PD-1 therapy. The role of tumor-derived exosomes in tumor response to immunotherapy was recapitulated by Wu et al, and they pointed out that tumor-derived exosomes should be studied and manipulated to provide clinical benefits and improve the clinical management of lung cancer [39] . Li et al reviewed the resistance mechanism to ICIs, especially in KRAS-mutant NSCLC, with a critical focus on metabolism remodeling mediated by the oncogenic KRAS pathway, and they argued that these alternated metabolic pathways could be promising approaches to overcome immunotherapy resistance [40] .…”
Section: Resistance Mechanism For Icis-based Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Their study raised the important role of circRNA in immune resistance and provided a potential targeted pathway "hsa_circ_0020714/miR-30a-5p/SOX4" to overcome resistance to anti-PD-1 therapy. The role of tumor-derived exosomes in tumor response to immunotherapy was recapitulated by Wu et al, and they pointed out that tumor-derived exosomes should be studied and manipulated to provide clinical benefits and improve the clinical management of lung cancer [39] . Li et al reviewed the resistance mechanism to ICIs, especially in KRAS-mutant NSCLC, with a critical focus on metabolism remodeling mediated by the oncogenic KRAS pathway, and they argued that these alternated metabolic pathways could be promising approaches to overcome immunotherapy resistance [40] .…”
Section: Resistance Mechanism For Icis-based Therapymentioning
confidence: 99%
“…Li et al . reviewed the resistance mechanism to ICIs, especially in KRAS-mutant NSCLC, with a critical focus on metabolism remodeling mediated by the oncogenic KRAS pathway, and they argued that these alternated metabolic pathways could be promising approaches to overcome immunotherapy resistance [ 40 ] . From the present clinical practice, Yu et al .…”
Section: Main Textmentioning
confidence: 99%
“…Mice with genetic loss of Nocth1 or Nocth2 facilitated SCLC tumorigenesis and formed non-neuroendocrine populations via regulation of RUNX2/REST pathway and STING (stimulator of interferon genes) ( Hong et al, 2022 ). Li Y. et al (2022) reported that Notch pathway was correlated with TIME in SCLC. Notch1 gene mutation was negatively linked to PD-L1 expression in SCLC patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, heterogeneity of immune checkpoint protein expression is a feature of NSCLC that limits the broad effectiveness of these therapies (Gettinger et al, 2015), with the absence of PD-L1 expression identified in both human and murine tumors with oncogenic KRAS and loss-of-function LKB1 mutations (Calles et al, 2015, Koyama et al, 2016, Skoulidis et al, 2015). The absence of checkpoint marker expression in pre-clinical models of dual KRAS; LKB1 mutated NSCLC corresponded with poor to no-responsiveness to checkpoint immunotherapy and subsequently effective treatments to durably target tumors that are non-responsive to immunotherapy or TKIs remain lacking (Skoulidis et al, 2018, Li et al, 2022).…”
Section: Introductionmentioning
confidence: 99%